2018
DOI: 10.1590/1678-5150-pvb-4590
|View full text |Cite
|
Sign up to set email alerts
|

Serosurvey of bluetongue, caprine arthritis-encephalitis (CAE) and Maedi-Visna in Barbary sheep (Ammotragus lervia) of a southern Brazilian zoo

Abstract: RESUMO.-[Estudo sorológico dos vírus da língua azul, da artrite-encefalite caprina e Maedi-Visna em aoudads (Ammotragus lervia) em um zoológico do Sul do Brasil.] A língua azul é uma doença infecciosa e não contagiosa, de notificação obrigatória, que pode afetar ruminantes domésticos e silvestres, transmitida por mosquitos do gênero Culicoides spp. Apesar da alta morbidade e mortalidade em ovelhas, o papel de animais silvestres no ciclo do vírus da língua azul é desconhecido. A artrite encefalite caprina (CAE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies have assessed BTV circulation in zoo parks worldwide, providing evidence of BTV exposure in different captive zoo animals (Frölich et al., 2005; Hourrigan & Klingsporn, 1975; Morikawa et al., 2018; Sanchez‐Romano et al., 2019; Sanderson et al., 2010). Clinical disease and mortality caused by BTV infection have also been reported in several zoo species, including threatened species (Mauroy et al., 2008; Baldini et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have assessed BTV circulation in zoo parks worldwide, providing evidence of BTV exposure in different captive zoo animals (Frölich et al., 2005; Hourrigan & Klingsporn, 1975; Morikawa et al., 2018; Sanchez‐Romano et al., 2019; Sanderson et al., 2010). Clinical disease and mortality caused by BTV infection have also been reported in several zoo species, including threatened species (Mauroy et al., 2008; Baldini et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vector development and proliferation is favorable in these regions (Dorneles et al, 2012). In Brazil, several studies have shown nationwide prevalence of bluetongue in different domestic and wild ruminant species (Costa, Lobato, Herrmann, Leite, & Haddad, 2006;Alves et al, 2009;Nogueira, Pituco, Stefano, Curci, & Cardoso, 2009;Tomich et al, 2009;Souza, Costa, Martinez, Costa, & Pinheiro, 2010;Mota et al, 2011;Dorneles et al, 2012;Pinheiro et al, 2013;Sbizera et al, 2017;Batista et al, 2018;Silva et al, 2018;Morikawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%